Connecting urban area with rural hinterland: A stepwise ecological security network construction approach in the urban–rural fringe. (May 2022) - Liang, Chen; Zeng, Jian; Zhang, Ruo-Chen; Wang, Qian-Wen
Graphical abstract: Highlights: Basic and connecting ESN are integrated to create an optimized ESN. The scarcity of transitional patches contributes most to the ecological disconnection in the URF. Optimal buffer width of rural structural, urban–rural connecting, and urban structural corridors was identified. This approach is effective in promoting urban–rural ecological connections. Abstract: Rapid and disordered urbanization has created a fragmented landscape, the urban–rural fringe (URF), which has led to the degradation of ecological connections between urban areas and rural hinterlands. The ecological security network (ESN) offers significant advantages for restoring interrupted urban–rural ecological processes. However, classic ESN construction approaches are ineffective in the URF when applied to a highly complex urbanization landscape. In this paper, a new approach for a stepwise ESN construction in the URF is proposed, which integrates the basic ESN and the connecting ESN to create an optimized ESN. Taking Xiamen as a case study, the ecological elements of the URF were extracted and reclassified for ESN construction. The scarcity of transitional patches and complexity of land cover were responsible for the lack of urban–rural connecting corridors. The final optimized ESN consisted of 19 source nodes with 7 rural structural corridors, 22 urban–rural connecting corridors, and 8 urban structural corridors. Moreover, the structural performance and spatial coverage of the ESN were both significantly improved after optimization. The optimal buffer widths of rural structural, urban–rural connecting, and urban structural corridors were 600 m, 180 m, and 120 m, respectively. This paper provides an operational framework of ESN construction adapted for the URF as well as management guidance for policymakers. It can support decisions for regulating urban growth and outlining ecological protection areas, thus contributing to sustainable urban development.